Pancreatectomy Versus Conservative Management for Pancreatic Cancer: A Question of Lead-time Bias. (October 2015) - Kendal, Wayne S.
Abstract : Objectives: Pancreatectomy is regarded as the only curative treatment for cancer of the pancreas. A population-based study was conducted to examine its efficacy within the general community. Methods: Overall and cancer-specific survivals were compared between individuals treated with pancreatectomy and those managed nonsurgically. Kaplan-Meier analysis was used, based on both time from diagnosis and attained age (age at diagnosis plus time from diagnosis). Results: A total of 7830 Surveillance Epidemiology and End Results cases of localized cancer of the pancreatic head were retrieved, diagnosed from 2000 to 2008. Median follow-up was 12 months; the pancreatectomy cohort was 5 years younger and had 7-fold less stage III disease. Overall and cancer-specific survivals were 17% and 21% at 5 years from time of diagnosis in the pancreatectomy cohort versus 2% and 4% in the nonsurgical cohort, respectively ( P <0.001). However, the overall and cancer-specific survival curves were nearly superimposed on each other when based on attained age. Moreover, the proportion of deaths attributable to pancreatic cancer exceeded 85% in both cohorts. Conclusions: A lead-time bias is hypothesized to explain the survival discrepancies seen between time from diagnosis and attained age analyses; the pancreatectomy cohort was diagnosed earlier, with less disease. If most of these individuals had occult metastases at diagnosis, which manifested later and caused death at similar ages as the nonsurgical cohort, their survival from time of diagnosis would appear speciously improved. A randomized controlled trial would be necessary to confirm whether or not the survival advantage ascribed to pancreatectomy should be attributed to lead-time bias.